Leaky Coupled Waveguide-Plasmon Modes for Enhanced Light–Matter Interaction - Fadi Sakran; Said Mahajna; Atef Shalabney (Sensors)
Plasmon waveguide resonances (PWRs) have been widely used to enhance the interaction between light and matter. PWRs have been used for chemical and biological sensing, molecular detection, and boosting other optical phenomena, such as Raman scattering and fluorescence. However, the performances of plasmon-waveguide-based structures have been investigated in the angular interrogation mode, and their potential in different spectral regions has hardly been explored. Moreover, the applications of PWRs have been limited to the weak light–matter coupling regime. In this study, we investigate leaky coupled waveguide plasmon resonances (LCWPRs) and explore their potential to enhance light–matter interaction in different spectral regions. In the weak coupling regime, we demonstrate the potential of LCWPRs for sensing in the near-IR region by detecting heavy water (D2O) and ethanol in water. The experimental results show spectral sensitivity of 15.2 nm/% and 1.41 nm/% for ethanol and D2O detection, respectively. Additionally, we show that LCWPRs can be used to achieve vibrational strong coupling (VSC) with organic molecules in the mid-IR region. We numerically show that the coupling between LCWPRs and the C=O stretching vibration of hexanal yields a Rabi splitting of 210 cm−1, putting the system in the VSC regime. We anticipate that LCWPRs will be a promising platform for enhanced spectroscopy, sensing, and strong coupling.